Prospección Radimétrica autotransportada - Coco, A.L.; Agost, Enrique José; Azamor, L.A. (Comisión Nacional de Energía Atómica (CNEA), 1977)
Fil:Coco, A.L. Comisión Nacional de Energía Atómica (CNEA). República Argentina